Exploring patients’ views regarding the support and rehabilitation needs of people living with myocardial ischaemia and no obstructive coronary arteries: a qualitative interview study - Simon Nichols; Colin Berry; Aynsley Cowie; Sarah Brown; Helen Humphreys; Susan Dawkes; Danielle Paddock (BMJ Open)
Objectives This study aimed to generate new qualitative insights to understand the rehabilitation needs of people living with a confirmed or presumed diagnosis of ischaemia with no obstructive coronary arteries (INOCA), explore which aspects of current cardiovascular prevention and rehabilitation programmes could meet the needs of people with INOCA and where adjustments (if any) may be appropriate.Design Semistructured qualitative interview study.Participants Interviews were undertaken (n=17; 88% female, age range 31–69 years) with people with a confirmed or presumed diagnosis of INOCA.Results Findings highlighted concerns around a lack of evidence-based guidance for cardiovascular prevention and rehabilitation programmes for patients with INOCA. Participants expressed a desire for modular cardiovascular prevention and rehabilitation programmes that could be accessed flexibly to accommodate episodic fluctuations in symptoms. Participants suggested that existing cardiovascular prevention and rehabilitation programme content needed adjustment including enhanced psychosocial support, supervised low-impact physical activity and specialist dietary advice and medication reviews. Additional elements specific to INOCA should be made available as appropriate including acute care planning and a module to provide information and support for female-specific issues. The importance of involving INOCA patients in the codesign of future programmes and associated training was emphasised.Conclusions People with INOCA are willing to engage with cardiovascular prevention and rehabilitation programmes and express a desire for more support. This patient group shares some barriers to rehabilitation programme attendance with other cardiac patient groups, but they also have specific concerns about the need for improved professional knowledge and evidence-based guidance regarding the management of INOCA. Cardiovascular rehabilitation programmes need to be delivered flexibly and individually tailored to ensure the relapsing and remitting nature of INOCA and associated support needs are addressed.